Pengaruh Status Sosial Ekonomi Orang Tua dan Kecerdasan Emosional terhadap Motivasi Atlet Tennis Meja PTM Otaka Gabus - Anugrah Mauludina Junianto; Ricko Irawan (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine the effect of parents' socioeconomic status on motivation, to determine whether intelligence has an influence on motivation, and lastly, to determine parents' socioeconomic status and emotional intelligence together have an influence on athlete motivation. This study uses the correlation method through a quantitative approach. The population in this study were all active athletes in PTM Otaka Gabus, while the sample used was 30 athletes with a total sampling technique/saturated sample and the sampling technique used was Non-Probality sampling. Aspects seen from the socio-economic status of parents are parental education, parental occupation, parental income, organization followed, and ownership of valuables. Aspects seen from emotional intelligence are recognizing one's own emotions, managing emotions, motivating oneself, recognizing other people's emotions, and building relationships. While the aspect that is seen from motivation is through intrinsic and extrinsic factors. The results of this study are that there is an effect of parents' socioeconomic status and emotional intelligence on athlete motivation together of 13.5%. It can be concluded that the relationship is unidirectional and has a positive value, meaning that if parents' socioeconomic status and emotional intelligence are high, then achievement motivation is high.